Penerapan Media Audio Untuk Meningkatkan Kemampuan Memahami Teks Lisan Dan Tulis Bahasa Inggris: Studi kasus Siswa Kelas XI-IPA MAN 4 Jombang - Luqman Zakariya; Muhtadi (FAI- Undar, 2022)
Effective and efficient learning media are needed to help students when facing learning situations that require an understanding of a number of alternative procedures (simple to complex) so that learning runs efficiently and practically. This study was designed using classroom research because the data taken included student and teacher activities, student learning outcomes, and student responses. These data are data obtained during the learning process and based on problems in the classroom. These problems will later be taken certain actions so that there is an improvement in each cycle From the results of student learning in each cycle, it was found that in each cycle, student learning outcomes increased. In the first cycle, students obtained an average score of 59.64 with a learning completeness of 35.71%. In the second cycle, students got an average score of 69.86 with 71.43% learning completeness. From the response analysis cycle 1 to cycle 3, it can be concluded that the responses that each cycle experienced an increase were the level of students' difficulty in learning meaning in the conversation that was heard, the level of understanding of students receiving the subject matter, the level of difficulty of students listening to the reading of meaning in the conversation that was heard, and belief. students about learning outcomes.